Formation mechanism of static pressure circumferential double-peak distribution in a centrifugal compressor under the action of downstream boundary. (July 2021) - Su, Botai; Yang, Ce; Zhang, Hanzhi; Shi, Xin; Fu, Li; Zhang, Hang
In the centrifugal compressor applied in the automobile turbochargers, the asymmetric structure of volute causes the non-uniform flow field in the impeller and compressor stall. The non-uniformity of the flow field in the compressor can be reflected by the casing-wall static pressure distribution. In this study, by removing the volute and directly imposing different simplified static pressure boundary conditions at the diffuser outlet, the formation mechanism of casing-wall static pressure circumferential double-peak distribution of the compressor is explored. It is found that the mass flow rate is redistributed at the impeller outlet due to local high static pressure induced by the volute tongue, which results in the formation of two airflow regions with high velocity in the diffuser, ultimately leading to the static pressure circumferential double-peak distribution in the diffuser and the impeller. Noted that because of the existence of the blades, the airflow regions with high and low velocity formed in the diffuser are locked within a limited range of one or more widths of the blade passage. When the number of blades in the compressor is large, the static pressure can appear as multi-peak distribution in the circumferential direction. Moreover, the result of the mass flow rate redistribution at the impeller outlet is determined by the static pressure distribution characteristics at the diffuser outlet.